THE EFFECT OF DIDACTIC TOOLS ON THE DEVELOPMENT OF PEDAGOGICAL AND SPECIAL SKILLS OF STUDENTS - Boburmirzo Bakhodirugli Kokiyev (Galaxy International Interdisciplinary Research Journal, 2023)
The impact of didactic tools on the development of pedagogical and special abilities of students is discussed. In addition, several examples of pedagogical and special skills development are given.